ChemInform Abstract: Structural, Optical and Electrical Properties of Cu2FeSnX4 (X: S, Se) Thin Films Prepared by Chemical Spray Pyrolysis. Issue 27 (18th June 2015) - Khadka, Dhruba B.; Kim, JunHo
Abstract Polycrystalline Cu2FeSnX4 (X: S, Se) thin films are prepared by chemical spray pyrolysis of a 2:1:1:10 molar solution of Cu(OAc)2, FeCl3, SnCl2, and CS(NH2)2 in DMSO/EtOH (1:1) on bare and Mo‐coated soda lime glass substrates (450 °C) followed by annealing in S or Se vapors (500—520 °C, 25 min), which results in improved surface texture and crystallinity.